LZCGT impact on GHG reductions in Scotland's new domestic buildings. (June 2019) - Burford, Neil; Onyango, Vincent; Wright, Frances
Abstract: One key means of reducing the greenhouse gas (GHG) emissions caused by heating, lighting and ventilating buildings is the use of more efficient low and zero-carbon generating technologies (LZCGTs). In recognition of this, Section 72 of the Climate Change (Scotland) Act 2009, requires Local Development Plans (LDPs) to include policies to ensure 'that all new buildings avoid a specified and rising proportion of the projected greenhouse gas emissions from their use, calculated on the basis of the approved design and plans for the specific development, through the installation and operation of LZCGT's.' This study utilises data collected from 5 Scottish Local Authorities who were early adopters of this policy and examines LZCGT uptake in a randomly selected sample of new domestic buildings and the impact the use of these technologies have on CO2 emission reduction. Quantitative data extracted from Standard Assessment Procedure reports submitted for Building Warrant was used to assess energy demand, energy consumption and CO2 emissions and identify trends in LZCGT uptake in the regions studied. This paper provides a number of key insights and recommendations that may foster greater and more impactful use of LZCGTs in Scotland. Highlights: Space Heating largest single contributor to energy demand, energy consumption and CO2 emissions. Extent and type of LZCGT varies regionally with areas off the gas grid demonstrating greater uptake. Low carbon technologies dominate with little evidence of scaled technologies or energy storage. LZCGT provision is being incentivised over energy conservation measures. Section 3 F policies ideally placed to address design orientated approaches to GHG reduction.